2022
DOI: 10.3390/fermentation8040146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhodanese Enzyme Addition on Rumen Fermentation, Cyanide Concentration, and Feed Utilization in Beef Cattle Receiving Various Levels of Fresh Cassava Root

Abstract: Fresh cassava root is not recommended for animal feeding due to high quantities of hydrocyanic acid (HCN), which produces symptoms of poisoning. The purpose of this study was to find out how a rhodanese enzyme addition affects rumen fermentation, HCN content, feed utilization, and blood metabolites in beef calves fed fresh cassava root. Four Thai native beef cattle with an initial body weight (BW) of 95 ± 10.0 kg (1–1.5 years old) were randomly allocated to receive fresh cassava root containing HCN at 0, 300, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…When CR containing HCN at 600 mg/kg DM was supplemented, total intake increased by 14.8% when compared to CR containing HCN at 300 mg/kg DM. In agreement, Supapong et al 31 discovered that when CR levels increased, it also increased the total amount of feed that was consumed by the animals. Fresh cassava roots are typically more palatable and offer a more appealing taste and texture compared to the dried form, resulting in increased feed intake 4 , 6 .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…When CR containing HCN at 600 mg/kg DM was supplemented, total intake increased by 14.8% when compared to CR containing HCN at 300 mg/kg DM. In agreement, Supapong et al 31 discovered that when CR levels increased, it also increased the total amount of feed that was consumed by the animals. Fresh cassava roots are typically more palatable and offer a more appealing taste and texture compared to the dried form, resulting in increased feed intake 4 , 6 .…”
Section: Discussionsupporting
confidence: 58%
“…When animals consume feed with a high NFC content, they can rapidly acquire a significant amount of energy. The improved palatability of the feed can stimulate their appetite, encouraging them to consume more of the NFC-rich feed 4 , 6 , 31 . As a result, nutritional intake varies depending on how much CR was provided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ruminants, the levels of rhodanese activity are high in the rumen epithelium, hepatocytes, and kidney cortex, resulting in the production of thiocyanate before its excretion in urine 13 . Previous research has shown that adding rhodanese in the presence of CN improves rumen fermentation characteristics in vitro (e.g., increasing cumulative gas production, in vitro digestibility, and volatile fatty acid concentration) 14 and in vivo (e.g., increasing propionate concentration) 15 .…”
Section: Introductionmentioning
confidence: 99%